IMPROVING STUDENTS VOCABULARY MASTERY BY USING KIDS SONGS (SD NEGERI 022 KAMPAR, RIAU) - wida rianti (Universitas Pahlawan Tuanku Tambusai, 2016)
At the beginning of this study, IVB grade students in 022 primary schools in Kampar face some problems in mastering English vocabulary. Some vocabulary learning model has been applied to improve their vocabulary. However, the study failed to increase their vocabulary. These circumstances affect their learning outcomes. Because of the lack of vocabulary, most of them do not reach the predetermined KKM. Therefore, this study was conducted. The purpose of this study was to clarify whether the use of children's songs can increase the students' vocabulary and to identify the factors that influence changes in their vocabulary for the use of a children's song. This research was carried out with the design of classroom action research during two cycles. The results showed an increased level of positive vocabulary. Their ability to give meaning to a vocabulary that have been studied increased from 70 in cycle 1 to 87 in cycle 2. their ability in spelling also increased from 57 in cycle 1 to 86 in cycle 2. Then, their ability in using vocabulary appropriate to the context of the sentence also increased, from 75 in cycle 1 to 84 in cycle 2. In addition, the factors affecting changes in vocabulary they also identified, namely the use of a children's song that is interesting, learning activities for the use of the children's song gives way to the them to pay attention to spelling, meaning, and how to use koskata in the right context and learning activities also provide an opportunity for repetition of new vocabulary.